P80 Assessment of association between duration of oxygen therapy in children with chronic lung disease of prematurity (cldp) and management of pda. (15th November 2017) - Zafar, A; Alifieraki, S; Bhatt, J
Abstract : Background: The presence of hemodynamically significant Patent Ductus arteriosus (PDA) is associated with the development and severity of chronic lung disease of prematurity (CLDP). Pulmonary hypertension (PHTN) is also associated with CLDP, may precede and contribute to its development and severity. We explored the relationship between the flow rate as well as the duration of home oxygen therapy (Home O2) (surrogate for severity of CLDP) in children with CLDP and interplay between the presence or absence of PDA, mode of managing PDA as well as PHTN. Setting: Tertiary CLDP service. Methods: Retrospective observational study All infants (median gestational age 26 weeks, range 23 to 35), born between 2009 and 2016, were included (n=172; 96 males). We excluded data for infants where there were incomplete records for ECHO or loss of follow-up due to management of further care in other centres. The date oxygen was discontinued by following a structured weaning protocol is prospectively recorded to calculate the length of home oxygen therapy. The presence or absence of PDA and if present whether this was managed medically or surgically as well as the presence or absence of PHTN (assessed by echocardiography) was recorded. Results: Conclusions: In our cohort, there was no significant difference between the duration of home oxygen therapy and the presence or absence of PDA and if present whether it was medically or surgically managed. Similarly, there was no significant difference between duration of home in presence or absence of pulmonary hypertension. Reference: Clyman, Ronald I. The role of patent ductus arteriosus and its treatments in the development of bronchopulmonary dysplasia. Seminars in Perinatology2013;37(2):102–107. PMC . Web. 20 July, 2017.